Clonal cytopenia of undetermined significance: definitions, risk and therapeutic targets - Taborda, Cristian C.; Zeidan, Amer M.; Mendez, Lourdes M. (Frontiers in Hematology, 2024)
Cancer-related somatic genetic alterations are detectable in the blood of individuals without hematologic malignancy, reflecting the outgrowth of a mutated stem/progenitor cell population, a phenomenon termed clonal hematopoiesis (CH). When accompanied by an unexplained cytopenia(s), CH is further refined to clonal cytopenia of undetermined significance (CCUS) whereas, the finding of a mutation/alteration in the setting of a normal complement of blood counts is called clonal hematopoiesis of indeterminate potential (CHIP). CHIP and CCUS are now recognized precursor conditions to myeloid neoplasms. Advances in the understanding of the epidemiology and clonal metrics associated with evolution to a myeloid malignancy has permitted the elaboration of risk stratification tools poised for use in the clinic and initial clinical investigations seeking to disrupt the natural history of high risk CHIP and CCUS. In this review, we focus on CCUS and the current understanding of its classification, risk stratification and potential therapeutic targets